ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI PADI SAWAH DI DESA TORIBULU KECAMATAN TORIBULU KABUPATEN PARIGI MOUTONG - Rizal Rizal (Universitas Tadulako, 2014)
The purpose of this study was to analyze the effect of inputs on wetland rice production and to determine their efficiency on wetland rice production in Toribulu Village of Toribulu Sub District, Parigi Moutong District. This study was conducted during March to May 2014. The number of respondents was 33 farmers out of 129 wetland rice farmer population selected using a simple random sampling technique. Data was analyzed using the cobb-douglas function and efficiency analysis. The input factors i.e land area (X1), seeds (X2), NPK fertilizer (X3), labor (X4), and pesticides (X5) both simultane ouslyand partially had significant effecton the rice production (Y). The coefficient of determination (R2) was 0.983 indicating that 98.3% of the variation in the variable factors of the rice production can be explained by all variables observed (Xi), while 1.7% is caused byother factors not included in the model. The efficiency scores of land area (X1), NPK fertilizer (X3), labor (X4), and pesticides (X5) were greater than 1 while seed (X2) was less than 1 suggesting that the former inputs used in the wetland rice production are not yet efficient but the latter is efficient in terms of price.